2021
DOI: 10.1007/s11695-021-05264-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Producing Cell Expansion in Wistar Rats. Changes to Islet Architecture After Sleeve Gastrectomy

Abstract: Purpose Many studies about bariatric surgery have analyzed the effect of sleeve gastrectomy (SG) on glucose improvement, beta-cell mass, and islet size modification. The effects of SG on the other endocrine cells of the pancreas, such as the alpha-cell population, and their regulatory mechanisms remain less studied. Materials and Methods We focused our work on the changes in the alpha-cell population after SG in a healthy model of Wistar rats. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…(28) Another research indicated that SG combined with pancreatic omentoplasty significantly reduces IL-1 levels and increases pancreatic β cell expression in rats with T2DM. (29) The decrease in IL-10 levels found in all three groups is consistent with previous studies stating that levels of anti-inflammatory cytokines, including IL-10, decrease in morbidly obese patients with sleep apnea. (31) IL-10 is known to inhibit inflammation by increasing immune responses during inflammatory events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(28) Another research indicated that SG combined with pancreatic omentoplasty significantly reduces IL-1 levels and increases pancreatic β cell expression in rats with T2DM. (29) The decrease in IL-10 levels found in all three groups is consistent with previous studies stating that levels of anti-inflammatory cytokines, including IL-10, decrease in morbidly obese patients with sleep apnea. (31) IL-10 is known to inhibit inflammation by increasing immune responses during inflammatory events.…”
Section: Discussionsupporting
confidence: 91%
“…(27) Furthermore, based on another study on rats, SG was found to expand the alpha-cell population at the expense of betacells, contributing to increased glucagon response without affecting plasma glucose levels. (29) Obesity's surplus adipose tissue influences metabolism by releasing hormones, glycerol, and various substances like leptin, cytokines, adiponectin, and pro-inflammatory agents, as well as by liberating Non-esterified fatty acids (NEFA). The rise in HOMA-IR levels among the control group indicates insulin resistance induced by obesity and DM.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated glucagon: insulin ratios have been reported in diabetic-GK rats after SG, and an early increase in serum glucagon levels has been reported in patients. These findings are consistent with what was observed in previous studies by our group reporting a long-term increase in pancreatic alpha cell mass in healthy rodents after SG with potent glucagon secretion capable of buffering exogenous insulin administration ( 56 ). This finding could explain the improved insulin secretion reported after SG because beta cell-expressing GCGR is activated by glucagon in rodents.…”
Section: Glucagon and Metabolic Surgerysupporting
confidence: 93%
“…Liu et al proposed long-term recovery of insulin sensitivity without beta-cell dysfunction as an answer to the question [ 24 ], but a recent work showed loss of beta-cell mass and a strong increase in alpha-cell mass in Wistar rats twelve weeks after SG. Trans-differentiation of the beta-cell population under stressful situations with loss of beta-cell markers such as PDX-1 and gain of alpha-cell markers such as Pax-6 and Arx has been shown [ 25 ] ( Figure 2 ). Moreover, this is supported by studies performed on mice outside the scope of bariatric surgery where alpha-cell populations labeled with Gcg-Cre lineage tracers showed a dilution of the marker at the expense of the beta-cell population throughout life [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, RYGB is also able to cause an increase in the alpha-cell population in mice six months after the operation, including a loss of beta identity markers such as PDX-1 and a gain of alpha-cell markers such as ARX in the islets ( Figure 2 ). All of this suggests long-term trans-differentiation of beta-cells into alpha-cells after surgery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%